2012
DOI: 10.1021/np300295h
|View full text |Cite
|
Sign up to set email alerts
|

Antiausterity Agents from Uvaria dac and Their Preferential Cytotoxic Activity against Human Pancreatic Cancer Cell Lines in a Nutrient-Deprived Condition

Abstract: Human pancreatic cancer cell lines are known for their inherent tolerance to nutrition starvation, which enables them to survive under a hypovascular (austerity) tumor microenvironment. The search for agents that preferentially retard the survival of cancer cells under low nutrition conditions (antiausterity agent) is a novel approach to anticancer drug discovery. In this study, it was found that a dichloromethane extract of the stem of Uvaria dac preferentially inhibited PANC-1 human pancreatic cancer cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Among the 5 plant extracts sensitizing breast cancer cells to TRAIL, U. dac and its active constituent (+) grandifloracin showed anti-austerity activity against PANC-1 human pancreatic cancer cells in a nutrition-deficient tumor-mimicking environment (18). The extract of A. vulgaris has been reported to have cytotoxicity against MCF-7 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 5 plant extracts sensitizing breast cancer cells to TRAIL, U. dac and its active constituent (+) grandifloracin showed anti-austerity activity against PANC-1 human pancreatic cancer cells in a nutrition-deficient tumor-mimicking environment (18). The extract of A. vulgaris has been reported to have cytotoxicity against MCF-7 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Over 130 compounds are identified in various organs of the tree of A. altilis, more than 70 of which derived from the phenylpropanoid pathway, including a number of prenylated dihydrochalcones [16][17][18][19][20][21][22][23][24][25], prenylated flavonoids [21][22][23][25][26][27][28][29][30][31][32], and prenylated aurones [25,33] together with some triterpenoids and phenolic compounds [34][35][36][37] ( Fig. 1-4).…”
Section: Chemical Constituents Of a Altilismentioning
confidence: 99%
“…Based on this strategy, many reports demonstrated that there were many natural products possessed antiausterity activity from medicinal plants such as Artocarpus altilis, Boesenbergia pandurata, Uvaria dac, Caesalpinia sappan, etc. [16][17][18][19]. In this chapter, we focus on A. altilis.…”
Section: Introductionmentioning
confidence: 99%
“…A single flower at the end of twig reaches 6-12 cm diameter when blooming. Phytochemical investigation of U. grandiflora demonstrated the presence of several groups of natural chemical, including polyoxygenated cyclohexenes and aromatic derivatives, also showed interesting antitumour, antimalarial [1][2][3][4] , and antipancreatic cancer activities 5,6 . Polyoxygenated cyclohexenes have a rather simple molecular skeleton of 1-methylcyclohex-4-ene.…”
Section: Introductionmentioning
confidence: 99%